Whistle‐blowing and the incentive to hire. - De Mot, Jef; Mungan, Murat C. (Economic Inquiry, 2024)
We consider a previously neglected cost of whistle‐blower awards: employers may base their hiring decisions, on the margin, not on the productivity of an employee but rather on the probability that the employee will become a whistle‐blower. We develop a three‐stage model to examine how productivity losses due to distortions at the hiring stage influence optimal whistle‐blower rewards. We characterize optimal rewards for whistle‐blowing, and show that when rewards can be chosen according to either the benefits of the employer from offending or the productivity of the worker being hired, productivity‐based rewards are superior to benefit‐based rewards.